Physiological outcomes of calming behaviors support the resilience hypothesis in horses. Issue 1 (December 2018) - Scopa, Chiara; Palagi, Elisabetta; Sighieri, Claudio; Baragli, Paolo
Abstract To manage a stressful stimulus animals react both behaviorally and physiologically to restore the homeostasis. In stable horses, a stressful stimulus can be represented by social separation, riding discomfort or the presence of novel objects in their environment. Although Heart Rate Variability is a common indicator of stress levels in horses, the behavioral mechanisms concurrently occurring under stressful conditions are still unknown. The sudden inflation of a balloon was administered to 33 horses. Video-recording of self-directed behaviors (snore, vacuum chewing, snort, head/body shaking) and monitoring of heart activity (HR and SDRR) were conducted for five minutes before (Pre-test) and after the stimulus administration (Stress-test). During the Stress-test, only snore and vacuum chewing increased and a significant increase was also recorded in both HR and SDRR. Moreover, the snore variation between the two conditions showed a significant correlation with the variation of both HR and SDRR. With the snore acting as stress-releasing behavior to restore basal condition, the homeostasis recovered via the enactment of such behavior could be physiologically expressed by an increasing vagal activity. Hence, the capacity to maintain homeostasis (resilience) could correspond to a prevalence of parasympathetic control on heart activity, intervening when certain behaviors are performed.